Bone Metabolism and Histomorphometric Changes in Murine Models Treated with Sclerostin Antibody: A Systematic Review - Das, Srijit; Sakthiswary, Rajalingham (Current Drug Targets, 2013)
Preventing osteoporotic fractures in millions of individuals may significantly reduce the associated morbidity and health-care expenditures incurred. As such, the search for newer anti-osteoporotic agents has been ongoing for years. Genetic studies have proven that the secreted protein sclerostin is one of the main culprits, which negatively regulates the bone formation. Recently, sclerostin-neutralizing monoclonal antibodies (Scl-Ab) in rodent studies have shown positive effects on bone homeostasis. An extensive search of the literature was performed in the BIOSIS, Cinahl, EMBASE, Pub-Med, Web of Science and Cochrane Library databases to evaluate the published murine studies on the effects of Scl-Ab on the bone metabolism and histomorphometric parameters. Our systematic review depicts a significant association between Scl-Ab administration and improvement in bone formation, bone density, bone volume and trabecular thickness.
Keywords: bone histomorphometry